Review on Frequency Agile Radar Seeker - Quan Yinghui, Fang Wen, Gao Xia, Ruan Feng, Li Yachao, Xing Mengdao (Editorial Office of Aero Weaponry, 2021)
Frequency agile radar has excellent low intercept and electronic countermeasures performance. In this paper, the research results of anti-main-lobes deceptive jamming of radar seeker are briefly reviewed, and the basic concepts and technical characteristics of frequency agile radar seeker are described. Then, the research results of frequency agile radar seeker at home and abroad are introduced, and the advantages and disadvantages of three frequency agile waveforms and the research progress of each signal processing technology are summarized. Finally, the development of adaptive frequency agility and multi-parameter combined agility radar seeker technology is prospected based on the future battlefield complex electromagnetic environment and seeker development trend.